The Effect of the External Factor in Community Mobility and it’s Reflection on Democratric Transition - Marjin, Hussein (Jordan Journal of Social Sciences, 2021)
Despite the fact that the social movement in Libya witnessed encouragement and support from abroad at a stage of its development, with the aim of overthrowing the political system and protecting its interests, the external factor can not initiate a movement that rejected the broad scope witnessed by Libya, Political, economic, social, cultural or technological issues. This paper aims at defining the concept and reasons of the external role in the case of Libya, in addition to determining the stages of development of the external role, and clarifying the results and their effects on the issue of democratic transition. Security to Council resolutions 1970- 1973, in accordance with Chapter VII of the Charter of the United Nations, which allows the Security Council to take all actions once the threat of peace happened, and lacke of clear plans and programs by the external actors, i.e. regional and international powers to overcome the collapse of the state institutions, and instead of supporting to create and promote the democratic transition they focused on their national interests. The local forces benefited from the for external intervention to stabilize their force in Libya. The results of the paper to confirm that the success of the process of democratic transition in Libya depends on the process of internal and external balances and consensus.